A rapid and highly specific technique to detect hepatitis C RNA in frozen sections of liver. - Sergi, Consolato M.; Goeser, Tobias; Otto, Gerd; Otto, Herwart F.; Hofmann, Walter J. (Journal of clinical pathology, 1996)
AIMS: To develop a polymerase chain reaction (PCR) based technique that would permit the rapid and highly specific detection of hepatitis C virus (HCV) RNA extracted from frozen liver tissue. METHODS: Samples of liver tissue from 18 patients undergoing orthotopic liver transplantation were studied. Nine patients were HCV positive. Total RNA was extracted from between one and 10 sections, 10 microns thick, from each tissue sample. HCV RNA was amplified by (1) conventional, multistep reverse transcription PCR (RT-PCR) and by (2) combined, single step RT-PCR using coupled oligonucleotide primers based on the sequence of the 5' untranslated region of the viral genome. Positive results were confirmed by dot blot analysis using a digoxigenin labelled oligoprobe (Alx 89). RESULTS: HCV RNA was detected in the nine HCV positive patients by both conventional and combined RT-PCR. HCV RNA was not detected in the HCV negative patients. As little as 500 ng total RNA was needed as the template to yield detectable amounts of amplified cDNA. The digoxigenin labelled oligoprobe hybridised with HCV RNA positive specimens only. CONCLUSIONS: The combined, single step RT-PCR is a rapid and sensitive technique for detecting HCV RNA in frozen liver tissue.